2016
DOI: 10.1172/jci86950
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular macrophages mediate the neurovascular and cognitive dysfunction associated with hypertension

Abstract: In this study we investigated the contribution of PVMs to the neurovascular and cognitive dysfunction induced by hypertension. We found that depletion of PVMs in models of chronic hypertension suppresses vascular oxidative stress and ameliorates the attendant impairment in neurovascular coupling and endothelium-dependent responses. Studies in bone marrow (BM) chimeras provided evidence that the dysfunction is mediated by ANGII acting on PVM AT1Rs resulting in NOX2-dependent ROS production. Importantly, concomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
358
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(395 citation statements)
references
References 68 publications
(110 reference statements)
18
358
2
Order By: Relevance
“…Importantly, lower plasma concentrations of HDL were reported to be associated with dementia (45). Considering that BBB leakage for small-size molecules (angiotensin II) can lead to cognitive defects (30), attenuated HDL/S1P 1 -dependent tightening of the BBB may be a risk factor for dementia. A recent study also demonstrated that BBB disruption is selective for small-size molecules at the early phase of murine ischemic brain injury (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, lower plasma concentrations of HDL were reported to be associated with dementia (45). Considering that BBB leakage for small-size molecules (angiotensin II) can lead to cognitive defects (30), attenuated HDL/S1P 1 -dependent tightening of the BBB may be a risk factor for dementia. A recent study also demonstrated that BBB disruption is selective for small-size molecules at the early phase of murine ischemic brain injury (46).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, chronic, but not acute, hypertension increases BBB leakage for small molecules, which causes cognitive impairment by enhancing exposure of angiotensin II to perivascular macrophage (30). Therefore, we asked whether deletion of endothelial S1pr1 and after BBB opening can affect recognition memory.…”
Section: Inflammatory Gene Expression and Cognitive Function In Earlymentioning
confidence: 99%
“…In addition, analysis showed a non-linear correlation between hippocampal TNF-α and blood pressure, suggesting that other factors could modulate the association between these parameters. For example, the breakdown of the bloodbrain barrier (BBB) induced by Ang II may be involved in the inflammatory process [31,32]. Indeed, a study from Marvar showed that Ang II is critical for BBB damage, independently of blood pressure [31].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that the cerebral inflammation induced by Ang II involves multiple pathways and cellular players, including but not limited to (i) the direct effects of circulating Ang II on AT1 receptors in cerebral vessels [51]; (ii) the damage to the BBB [32], which could facilitate the entry of Ang II to brain regions beyond the CVO network (i.e., the hippocampus); (iii) the consequent effects on microglia and astrocytes, leading to the expression of pro-inflammatory cytokines within the brain; and (iv) the entry of activated immune cells from the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, Faraco et al provide an exciting link between hypertension and cognitive decline (15). Specifically, they have shown that perivascular macrophages (PVMs) closely associate with cortical arterioles and that hypertension causes disruption of the blood-brain barrier, allowing Ang II to reach these cells.…”
Section: Perivascular Macrophages: the Missing Linkmentioning
confidence: 99%